Perkembangan Pengetahuan untuk mengabstraksi Makna-makna dan Penggunaan Sinkroni Strategi strategi lngatan. - Hamzah, Mohamad Daud (Penerbit Universiti Sains Malaysia, 1985)
This paper indicates that there are two approaches towards human memory, i.e. the 'constructive' and 'reconstructive' approaches. The constructive approach supports a contention that memory activities are basically activities engaged by an individual to construct the 'meanings' of the items tobe-remembered (or to-be-learned) based on the individual's comprehension of these items. Since memory activities involved the use of memory strategies it is argued that the function of memory strategies is to 'absorb' or 'abstract' meanings. However, it is also pointed out that this function would be poorly operative unless an individual could perform specific activities to abstract meanings. These activities are controlled by knowledge to abstract meanings which develops across age